An enzyme-linked immunosorbent assay (ELISA) using a recombinant (plasmodium falciparum) merozoite surface protein (P?MSP) as a seroepidemiological method for malaria in the Philippines - Sampang, Jennifer M. (1999)
A cross-sectional seroepidemiologic study using two types of serologic tests (with two kinds of antigens) in two different endemic populations (low and high) in the Philippines was done. The objective was to assess the usefulness of an enzyme-linked immunosorbent assay (ELISA) using a specific antigen, the Plasmodium falciparum merozoite surface protein (P?MSP1) vis-a-vis the indirect fluorescent antibody test (IFAT) using whole or crude parasite antigens in malaria seroepidemiology. Results showed no significant difference in the overall and age-specific seroprevalence of antibodies detected by IFAT between the study populations of Morong, Bataan (low endemic area) and Cabugao, Apayao (high endemic area). In both study areas however, antibody prevalence and concentration as detected by the IFAT increased with age. On the other hand, overall and age-specific seroprevalence of anti-P?MSP1 antibodies were significantly lower in the low endemic compared with the high endemic area. Moreover, prevalence and concentration of anti-P?MSP1 antibodies in the low endemic areas showed no age-dependence. In contrast, in the high endemic are, anti- P?MSP1 antibody prevalence and concentration were acquired in an age-dependent manner. In addition, presence of parasitaemia appeared to be associated with the prevalence of anti-P?MSP1 antibodies in the low endemic area but not in the high endemic area. This suggests that anti-P?MSP1 antibody prevalence is indicative of the prevalence of parasitaemia in a low endemic area while in the high endmic area it may be more indicative of the intensity of transmission. Thus the P?MSP1-ELISA may be used as a seroepidemiological method to estimate the parasite prevalence in a low endemic area and to determine the intensity of malaria transmission in a high endemic area.
Thesis (Master of Science in Public Health, Parasitology)--University of the Philippines Manila.
Keywords: Malaria; Enzyme-linked immunosorbent assay; Plasmodium falciparum